The Effect of Nonionic Surfactants on the Kinetics of Methane Hydrate Formation in Multiphase System - Khor Siak Foo; Omar Nashed; Bhajan Lal; Cornelius Borecho Bavoh; Azmi Mohd Shariff; Raj Deo Tewari (Colloids and Interfaces, 2022)
Gas hydrate inhibitors have proven to be the most feasible approach to controlling hydrate formation in flow assurance operational facilities. Due to the unsatisfactory performance of the traditional inhibitors, novel effective inhibitors are needed to replace the existing ones for safe operations within constrained budgets. This work presents experimental and modeling studies on the effects of nonionic surfactants as kinetic hydrate inhibitors. The kinetic methane hydrate inhibition impact of Tween-20, Tween-40, Tween-80, Span-20, Span-40, and Span-80 solutions was tested in a 1:1 mixture of a water and oil multiphase system at a concentration of 1.0% (v/v) and 2.0% (v/v), using a high-pressure autoclave cell at 8.70 MPa and 274.15 K. The results showed that Tween-80 effectively delays the hydrate nucleation time at 2.5% (v/v) by 868.1% compared to the blank sample. Tween-80 is more effective than PVP (a commercial kinetic hydrate inhibitor) in delaying the hydrate nucleation time. The adopted models could predict the methane hydrate induction time and rate of hydrate formation in an acceptable range with an APE of less than 6%. The findings in this study are useful for safely transporting hydrocarbons in multiphase oil systems with fewer hydrate plug threats.